2022
DOI: 10.1007/jhep09(2022)071
|View full text |Cite
|
Sign up to set email alerts
|

Interior of helical black holes

Abstract: We study the interior structure of five dimensional neutral helical black holes in Einstein gravity and charged helical black holes in Einstein-Maxwell gravity. Inside the neutral helical black holes, the systems evolve to a stable spacelike Kasner singularity. The metric field related to the helical deformation strength exhibits oscillation behavior close to the horizon at low temperature and small helical deformation strength. Inside the charged helical black holes, we show that the inner Cauchy horizon can … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…4 we verify that the expression (24) gives an excellent description of the bounces found numerically in §3. It may be noted that the equation (23) and solution (24) are somewhat similar, but not quite identical, to the approximate analytic description of 'Kasner inversions' of charged black holes obtained in [14,33]. A difference with the Kasner inversions is that here the metric component g t t continues to collapse towards zero across all transitions.…”
Section: Analytic Description Of the Extended Bouncementioning
confidence: 61%
See 1 more Smart Citation
“…4 we verify that the expression (24) gives an excellent description of the bounces found numerically in §3. It may be noted that the equation (23) and solution (24) are somewhat similar, but not quite identical, to the approximate analytic description of 'Kasner inversions' of charged black holes obtained in [14,33]. A difference with the Kasner inversions is that here the metric component g t t continues to collapse towards zero across all transitions.…”
Section: Analytic Description Of the Extended Bouncementioning
confidence: 61%
“…A recent body of work has demonstrated that a common feature of (minisuperspace) holographic interiors is the emergence of Kasner scaling towards the singularity [11,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. The negative cosmological constant becomes irrelevant at late interior times, and therefore the well-studied approach to spacelike singularities in gravity without a cosmological constant is recovered.…”
Section: Introductionmentioning
confidence: 99%
“…For example, we may consider flows which break translation invariance and thus describe phonons. Simple flows of this kind include those for which the dynamics are governed by ODEs [56][57][58][59][60]. We may also take the striped superconductor [61,62], but this is more complicated because the dynamics are governed by PDEs and would thus require more powerful numerical techniques.…”
Section: Jhep01(2023)007mentioning
confidence: 99%
“…The interior has subsequently been subjected to further study. This includes the introduction of additional field content and variation of coupling parameters [19][20][21][22][23], use of alternative black hole solutions [24][25][26], analysis of RG flows [27,28], as well as the construction of "no inner-horizon" theorems [29]. Interior solutions for the p-wave model are now also being investigated, with the analogous changes in geometry and matter fields being observed [30].…”
Section: Introductionmentioning
confidence: 99%